Design and Fabrication of Automated Stopper Mechanism with PLC-Controlled System and Ball Screw Mechanism - Fahriza Fadhila; Farid Triawan (ASEAN Journal for Science and Engineering in Materials, 2025)
The demand for high precision and efficiency in industrial cutting operations has driven the development of automated positioning mechanisms. Most traditional manual stopper systems in panel saws often suffer from inaccuracies, inefficiencies, and material waste. To address these issues, this study presents the design, implementation, and performance evaluation of a PLC-based automated stopper mechanism utilizing a ball screw system for precise linear motion. The system integrates a Programmable Logic Controller (PLC), stepper motor, ball screw mechanism, and Human-Machine Interface (HMI) to enable accurate positioning and real-time operator control. Performance tests validated the system’s reliability, precision, and suitability for industrial cutting applications. Speed evaluations confirmed that the stopper exceeded the 40 mm/s requirement, achieving 43.4 mm/s. Force resistance tests demonstrated structural stability under a 100 N load, with minimal deviations of 0.05 mm at 125 N and 0.10 mm at 150 N. Positioning accuracy tests further confirmed an average error of only 0.1 mm (0.005% deviation). The PLC executed motion commands with an average response time of 0.5 seconds, ensuring quick and reliable adjustments. These findings highlight the effectiveness of PLC-based automation in improving positioning accuracy, production speed, and overall usability in manufacturing environments.